Visceral adiposity index is associated with increased urinary albumin excretion: A population-based study. Issue 3 (June 2019) - Sun, Kan; Lin, Diaozhu; Li, Feng; Qi, Yiqin; Feng, Wanting; Ren, Meng; Yan, Li; Liu, Dan
Summary: Background: The effects of visceral fat accumulation on the renal damage have drawn much attention. We aimed to investigate the possible relationship between visceral adiposity and albuminuria. Methods: We included information from a population-based study in 9473 subjects aged 40 years or older. As a novel and valid indicator for visceral adipose function, visceral adiposity index (VAI) was determined by gender-specific equations and calculated using simple anthropometric and functional parameters. Increased urinary albumin excretion was defined as albumin-to-creatinine ratio (ACR) 30 mg/g or greater. Results: The prevalence rate of increased urinary albumin excretion was 6.6% in this population and gradually increased across VAI quartiles. Participants with higher VAI had elevated age, blood pressure, cholesterol, fasting insulin and decreased high density lipoprotein cholesterol and estimated glomerular filtration rate (eGFR) level. In multivariate logistic regression analysis, the adjusted odds ratios (ORs) of increased urinary albumin excretion for increasing VAI quartiles were 1.00 (reference), 1.29 (95% confidence intervals [CI] 0.94–1.76), 1.46 (95% CI 1.08–1.97) and 1.79 (95% CI 1.33–2.41). In subgroup analysis and after multiple adjustments, significant relation between VAI level and prevalent increased urinary albumin excretion was detected in women, younger subjects, non-obesity subjects, those without diabetes and those with eGFR ≥60 ml/min per 1.73 m 2 . Conclusion: Visceral fat accumulation evaluating by VAI is independently associated with increased urinary albumin excretion in middle-aged and elderly Chinese.